High‐Energy Mechanical Treatment Boosts Ion Transport in Nanocrystalline Li2B4O7. Issue 5 (2nd March 2016) - Wohlmuth, Dominik; Epp, Viktor; Stanje, Bernhard; Welsch, Anna‐Maria; Behrens, Harald; Wilkening, Martin
Abstract : In many cases fast solid ion conductors are characterized by a large number fraction of defects and vacant positions that enable the ions to move over long distances in a facile way. The introduction of structural disorder via high‐energy mechanical impact represents a very promising possibility to improve and to tune the transport properties of otherwise poorly conducting solids. Lithium tetraborate, Li2 B4 O7, in its single crystalline form or with an average crystallite size in the μm range, is known as a very poor Li ion conductor and can serve as a model compound to study the influence of structural disorder on ion dynamics. In the present study, we used high‐energy ball milling to prepare nanocrystalline defect‐rich Li2 B4 O7 characterized by a mean crystallite diameter of ca. 20 nm. With increasing milling time the sample became partly amorphous. Polycrystalline Li2 B4 O7 with crystallite sizes in the order of 100 nm served as starting material. The nanostructured samples obtained show dc conductivities σdc in the order of 2.5 × 10 −7 S/cm at 490 K which represents an increase by more than four orders of magnitude compared to the source material. While conductivity spectroscopy was applied to study the effect of different milling times on ionic conductivity in detail; Li ion self‐diffusion in nanostructured Li2 B4 O7 as well as in the starting material was investigated by variable‐temperature solid‐state 7 Li nuclear magnetic resonance (NMR) relaxometry. While the first is sensitive to long‐range ion transport, lithium NMR is able to access also short‐ranged ion motions.